(untitled) (Journal of Environmental Bioremediation and Toxicology, 2021)
Glucose levels in the blood are elevated because the pancreas’ b-cells produce less insulin or are more resistant to the hormone’s effects. Diabetes mellitus is a persistent metabolic condition. Insulin is linked to long-term difficulties in the metabolism of carbohydrates, fats, and proteins. The objective of this study was to determine kidney indices and serum electrolytes of diabetic patients attending Federal Teaching Hospital Gombe, Gombe State. In total, A total of 240 subjects were used for the analysis (200 diabetic and 40 control subjects) and were divided based on their ages and gender Face to face inter-view was used to collect the data and other possible clinical data associated with diabetes mellitus. Fasting venous blood sample was collected to assess serum kidney indices, weight and height were recorded. The result shows individual kidney abnormalities of elevated serum creatinine and urea, elevated level of chloride and reduced sodium and bicarbonate level, according to gender and age groups. Gender, aging, higher body mass indexes (BMI), kidney indices abnormalities and electrolytes imbalance, were the risk factors associated with diabetes mellitus that led to diabetic nephropathy which can increase morbidity and mortality in diabetes mellitus. Effective control of blood sugar can stop or prevent the progression of diabetes mellitus to all these complications.